2014
DOI: 10.1039/c4ra02139h
|View full text |Cite
|
Sign up to set email alerts
|

CO2concentration and pH alters subsurface microbial ecology at reservoir temperature and pressure

Abstract: Molecular ecology techniques are utilized to determine the impact of CO2 concentrations on microbial communities under reservoir temperature and pressure simulating geological carbon sequestration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 63 publications
0
17
1
Order By: Relevance
“…The samples were named after the wells they were obtained from and will be referred to by these identifiers throughout the article: BG (upgradient well, 0.0 mg l −1 CO 2(aq) ), MW3 (downgradient well, 1.53 g CO 2(aq) l −1 ), MW2 (downgradient well, 1.153 g CO 2(aq) l −1 ), MW1 (downgradient well, 0.006 g CO 2(aq) l −1 ) and MW4 (downgradient well, 0 g CO 2(aq) l −1 ). Studies describing site layout and geochemistry have previously been published (Trautz et al ., ; Gulliver et al ., ,b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples were named after the wells they were obtained from and will be referred to by these identifiers throughout the article: BG (upgradient well, 0.0 mg l −1 CO 2(aq) ), MW3 (downgradient well, 1.53 g CO 2(aq) l −1 ), MW2 (downgradient well, 1.153 g CO 2(aq) l −1 ), MW1 (downgradient well, 0.006 g CO 2(aq) l −1 ) and MW4 (downgradient well, 0 g CO 2(aq) l −1 ). Studies describing site layout and geochemistry have previously been published (Trautz et al ., ; Gulliver et al ., ,b).…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation of the microbial community structure in Plant Daniel samples using next generation Illumina 16S rRNA gene sequencing and metagenomic shotgun sequencing confirmed previous findings made using a pyrosequencing and cloning approach at the same site (Gulliver et al ., ,b). Overall, the diversity was reduced in samples with higher CO 2 concentrations compared to samples with little‐to‐no CO 2 The higher CO 2 concentration samples MW3 and MW2 (1.53 and 1.15 g CO 2 l −1 , respectively) were characterized by OTU counts 233 and 188, Chao1 measurements 350–385 and Shannon indices 2.5–3.9 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During CO2 sequestration, interactions of native or introduced microbial populations with the geochemically and physically altered subsurface might promote geochemical processes that are beneficial or detrimental to the long-term storage of CO2. Previous studies have demonstrated that after exposure to CO2, the microbial abundance in formation water from saline and freshwater aquifers decreased (Gulliver et al 2014a;Gulliver et al 2014b). Nevertheless, bacteria that produce acids as a byproduct of metabolism might dissolve carbonate minerals and increase metal ion mobility (Gulliver et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that after exposure to CO2, the microbial abundance in formation water from saline and freshwater aquifers decreased (Gulliver et al 2014a;Gulliver et al 2014b). Nevertheless, bacteria that produce acids as a byproduct of metabolism might dissolve carbonate minerals and increase metal ion mobility (Gulliver et al 2014a). The dissolution of feldspar (Welch et al 1999) and Fe(III) minerals (Glasauer et al 2003), and the precipitation of metal sulfides and silicate and carbonates (Schultze-Lam et al 1996) are examples of how bacteria could influence mineralogical characteristics.…”
Section: Introductionmentioning
confidence: 99%